2016
DOI: 10.7146/mediekultur.v32i61.22433
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal representations of gender in young children's popular culture

Abstract: Th is article poses questions regarding learning and representation in relation to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Machin and Thornborrow (2006) showed that women's agency in magazines is expressed only through the way they seduce men; nevertheless, Machin and van Leeuwen (2007) showed that in Vietnamese magazines, women are depicted as carrying out actual work strategically, and they are not depicted in a seductive way. Lindstrand, Insulander, & Selander (2016) examined the gender differences in a TV series and a mobile application about the same brand as examples of young children's popular culture. Although both media corroborate the stereotypical portrayal of girls as lazy and inferior to boys, the interactive modes in the application gave the children the freedom to participate in the creation of meaning and the social gender roles.…”
Section: Gender Representations In Mediamentioning
confidence: 99%
“…Machin and Thornborrow (2006) showed that women's agency in magazines is expressed only through the way they seduce men; nevertheless, Machin and van Leeuwen (2007) showed that in Vietnamese magazines, women are depicted as carrying out actual work strategically, and they are not depicted in a seductive way. Lindstrand, Insulander, & Selander (2016) examined the gender differences in a TV series and a mobile application about the same brand as examples of young children's popular culture. Although both media corroborate the stereotypical portrayal of girls as lazy and inferior to boys, the interactive modes in the application gave the children the freedom to participate in the creation of meaning and the social gender roles.…”
Section: Gender Representations In Mediamentioning
confidence: 99%
“…Gender issues have long been the focus of attention and sparked a lot of research in social and linguistic studies. Several studies have tackled gender representation from a multimodal perspective in different genres, including English language textbooks (Ahmad & Shah, 2019;Marefata & Marzban, 2014), TV commercials (Rubio, 2018), cinematic content (Guha et al, 2015) and young children's popular culture (Lindstrand et al, 2016). In these studies, the issue of how image representation and the combination of different participants contribute to constructing gender roles for men and women was examined.…”
Section: Gender Representation and Multimodal Discoursementioning
confidence: 99%
“…Cultures can have direct impacts on children preferences for toys that are "designed, packaged, and marketed to correspond with their masculine or feminine identities" (Kahlenberg & Hein, 2010, p. 830). Further, social norms and expectations are also linked to this approach (Lindstrand, Insulander, & Selander, 2016;Robinson, Smith, & Davies, 2017).…”
Section: Review Of Literaturementioning
confidence: 99%